2006
DOI: 10.1111/j.1365-2044.2006.04787.x
|View full text |Cite
|
Sign up to set email alerts
|

The LMA CTrachTM in airway resuscitation: six case reports

Abstract: SummaryWe report six patients with unexpected difficult airways who underwent tracheal intubation using the Laryngeal Mask Airway CTrach™. All these patients had failed orotracheal intubation using direct laryngoscopy and gum elastic bougie placement. Fibreoptic bronchoscopy failed in two of these patients due to blood and secretions in the airway. This report describes the successful use of this new intubating laryngeal mask in these cases, all of whom were intubated on the first attempt with this new device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Reports have been published on the use of the CTrach in patients with normal airways [22,23], in morbidly obese patients [24], and in patients with anticipated difficult airways [25][26][27]. In the study of patients with normal airways, tracheal intubation was successful at the first atttempt in 100% of cases.…”
Section: ó 2009 the Authorsmentioning
confidence: 99%
“…Reports have been published on the use of the CTrach in patients with normal airways [22,23], in morbidly obese patients [24], and in patients with anticipated difficult airways [25][26][27]. In the study of patients with normal airways, tracheal intubation was successful at the first atttempt in 100% of cases.…”
Section: ó 2009 the Authorsmentioning
confidence: 99%
“…However supraglottic devices are useful alternatives provided the mouth opening is adequate and there is no oropharyngeal pathology 10,11,12 . The CTrach provides a patent airway conduit 12,13 and the intubation can be facilitated under direct vision.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al reported 100% first attempt intubation success rate when CTrach was used in 84 normal paralysed patients 4 . It has also been successfully used in patients with potential 9,11,12 or unanticipated difficult airway 10 .…”
Section: Resultsmentioning
confidence: 99%
“…4 Recently the laryngeal mask airway CTrach™ (LMA CTrach™) has been used for tracheal intubation in patients with unexpected difficult airways. 5 The LMA CTrach™ is identical to the ILMA but in addition it has integrated fibreoptic that provides a view of the larynx that allows visualization of the endotracheal tube as it is advanced through the vocal cords. Due to potential difficulty in secondary tracheal intubation using the LMA® -Unique, either the LMA® -Classic or ILMA should be available for managing difficult intubation.…”
Section: Tracheal Intubation Through a Single Use Laryngeal Mask Airwmentioning
confidence: 99%